SILURIAN AND DEVONIAN NEPIOMORPH BIVALVES FROM BOLIVIA (Ameghiniana, 2016)
Rare nepiomorph bivalves from the Silurian and the Devonian beds of the Central Andes Basin of Western Gondwanaland are herein presented. They were collected in four scattered outcrops in the Eastern Andes Cordillera and southern Interandean Bolivia. A total of 58 specimens of medium preservation were studied. Almost all of them are Ludlowian to Pridolian in age: Praecardium sp. A, Cardiola fluctuans Barrande, Dualina secunda Barrande, and one species is of Eifelian age: Praecardium sudamericanum (Kozlowski). This is both, the first report of the genus Praecardium Barrande of Ludlowian to Pridolian age in this part of Gondwanaland and the first occurrence of the species Cardiola fluctuans Barrande in Bolivia. Through findings in the centre of the Silurian–Devonian Central Andes Basin (Pongo and Chaquimayu localities), this paper confirms the cosmopolitism of Dualina secunda Barrande. This research contributes to the as yet inaccurately known Silurian and Devonian paleogeography of the Central Andes Basin and to update old systematic descriptions of nepiomorph bivalves from late 19th and early 20th centuries.Resumen. BIVALVOS NEPIOMORFIOS DEL SILÚRICO Y DEVÓNICO DE BOLIVIA. Se dan a conocer bivalvos nepiomorfios muy poco frecuentes en la fauna siluro–devónica de la Cuenca de los Andes Centrales del Gondwana Occidental, a partir de hallazgos en cuatro afloramientos dispersos en Cordillera Oriental e Interandino sur de Bolivia. Se describen 58 ejemplares de variable preservación, de los cuales casi todos son ludlowianos a pridolianos: Praecardium sp. A, Cardiola fluctuans Barrande, Dualina secunda Barrande y una forma eifeliana: Praecardium sudamericanum (Kozlowski). Es la primera vez que se reporta en el Ludlowiano–Pridoliano de esta parte del Gondwana el género Praecardium Barrande. Es también la primera vez que se registra en Bolivia la especie Cardiola fluctuans Barrande. Se confirma el carácter cosmopolita de Dualina secunda Barrande con hallazgos en el centro de la Cuenca de los Andes Centrales (en Pongo y Chaquimayu). Este trabajo contribuye al conocimiento de las paleogeografías siluro–devónicas de la Cuenca de los Andes Centrales, hasta aquí poco precisas, y actualiza además viejas descripciones sistemáticas de bivalvos nepiomorfios hechas en el siglo 19 y principios del 20.